Examination of the properties of IMRT and VMAT beams and evaluation against pre-treatment quality assurance results. (11th March 2015) - Crowe, S B; Kairn, T; Middlebrook, N; Sutherland, B; Hill, B; Kenny, J; Langton, C M; Trapp, J V
Abstract: This study aimed to provide a detailed evaluation and comparison of a range of modulated beam evaluation metrics, in terms of their correlation with QA testing results and their variation between treatment sites, for a large number of treatments. Ten metrics including the modulation index (MI), fluence map complexity, modulation complexity score (MCS), mean aperture displacement (MAD) and small aperture score (SAS) were evaluated for 546 beams from 122 intensity modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT) treatment plans targeting the anus, rectum, endometrium, brain, head and neck and prostate. The calculated sets of metrics were evaluated in terms of their relationships to each other and their correlation with the results of electronic portal imaging based quality assurance (QA) evaluations of the treatment beams. Evaluation of the MI, MAD and SAS suggested that beams used in treatments of the anus, rectum, head and neck were more complex than the prostate and brain treatment beams. Seven of the ten beam complexity metrics were found to be strongly correlated with the results from QA testing of the IMRT beams ( p < 0.00008). For example, values of SAS (with multileaf collimator apertures narrower than 10 mm defined as 'small') less than 0.2 also identified QA passing IMRT beams with 100% specificity. However, few of the metrics are correlated with the results from QA testing of the VMAT beams, whether they were evaluated as whole 360° arcs or as 60° sub-arcs. Select evaluation of beam complexity metrics (at least MI, MCS and SAS) is therefore recommended, as an intermediate step in the IMRT QA chain. Such evaluation may also be useful as a means of periodically reviewing VMAT planning or optimiser performance.